2005
DOI: 10.1208/pt060231
|View full text |Cite
|
Sign up to set email alerts
|

Papain entrapment in alginate beads for stability improvement and site-specific delivery: Physicochemical characterization and factorial optimization using neural network modeling

Abstract: This work examines the influence of various process parameters (like sodium alginate concentration, calcium chloride concentration, and hardening time) on papain entrapped in ionotropically cross-linked alginate beads for stability improvement and site-specific delivery to the small intestine using neural network modeling. A 3(3) full-factorial design and feed-forward neural network with multilayer perceptron was used to investigate the effect of process variables on percentage of entrapment, time required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 31 publications
4
50
0
1
Order By: Relevance
“…Available studies where papain was immobilized in ionotropically crosslinked sodium alginate and kappa-carrageenan gel beads reported that 90% of papain was released from formulation within 50 minutes in simulated gastric ‰uid. 22,23) As a result papain would remain almost inactive as well as lose its structural integrity at low pH of stomach (pH 1.2). Hence su‹-cient amount of papain would not reach to the target site for digestion of peptides/proteins.…”
Section: Formulation Variablesmentioning
confidence: 99%
“…Available studies where papain was immobilized in ionotropically crosslinked sodium alginate and kappa-carrageenan gel beads reported that 90% of papain was released from formulation within 50 minutes in simulated gastric ‰uid. 22,23) As a result papain would remain almost inactive as well as lose its structural integrity at low pH of stomach (pH 1.2). Hence su‹-cient amount of papain would not reach to the target site for digestion of peptides/proteins.…”
Section: Formulation Variablesmentioning
confidence: 99%
“…The added droplets were retained in the calcium chloride solution for 15 min to complete the curing reaction and to produce spherical rigid microcapsules. The time of gel formation influences the drug loading efficiency and also the cohesion of the gel (17). The drug loading efficiency as a function of microcapsules formation time (time of contact with CaCl 2 solution) is reported in Fig.…”
Section: Preparation Of Microcapsulesmentioning
confidence: 99%
“…Figure 5 depicts the phenytoin release profiles from all alginate and alginate-chitosan microparticle formulations manufactured in the one-stage procedure. The times for 50% and 90% of drug to be released (t 50% and t 90% , respectively), as the parameters suitable for comparing the different formulations (Takka and Acarturk 1999;Sankalia et al 2005), are shown in Table 3. We found that the influence of chitosan coating on phenytoin release cannot be clearly deduced.…”
Section: Drug Assaymentioning
confidence: 99%